Media Consuming in Children: Child Development, Babyhood (0- 2), Early Childhood, Interests - Köksalan, Bahadir; Aldim, Umit Ferit; Göğebakan, Şahin (IGI Global, 2022)
Media consuption is a term in “sociology” that describes the individuals that organize information on the basis of the use of produced goods, rather than on the axis of services and production. Mediums that fall under the scope of media consumption include radio, television, computer, mobile phones, newspaper, and magazine formats. The usage patterns and applications of these tools are internet, music, movies, games, etc. Among children between the ages of 5 and 8, those who do not use computers represent a small percentage of 10%. Even within this age group, a large majority know how to use computers. More than half of children under the age of 8 have played games and watched videos at least once via a smartphone, iPod, iPad or similar device. According to a US study, children spend about 9 hours a day on the screen. Besides this, despite all the options, listening to music and watching television for children and young people continue to be a favorite activity. This paper further explores the impact of media consumption on children’s development. © 2022 by IGI Global. All rights reserved.
Keywords: Computer games; Computer music; Smartphones; Age groups; Child's development; Early childhoods; Media consumption; Movie games; Smart phones; Usage patterns; Young peoples; Technology transfer